Dampak Penggunaan Media Pembelajaran Koran Digital Terhadap Penguatan Civic Literacy di SMP Negeri 1 Terbanggi Besar pada Tahun Ajaran 2021/2022 - Wulandari, Selva; Yanzi, Hermi; Rohman, Rohman (urn:nbn:de:0000-jips.v5i10, 2024)
Teachers as educators are the main actors in the process of delivering knowledge or transferring knowledge in the classroom. Therefore, one of the skills that must be developed by teachers is the skill in utilizing digital media as a medium in learning that can support success in achieving these learning goals. In addition, other skills that must be developed are critical thinking skills, where this can be manifested also in civic literacy which is of course very important in preparing students to face global challenges, especially in the field of education. The research method used is descriptive method with a quantitative approach. Data collection techniques used the main technique, namely questionnaires and supporting techniques, namely interviews. The tool for analyzing the data in this study is using SPSS version 20. The results show that the use of digital newspaper-based media has a positive effect on strengthening students' civic literacy. Because it is seen from the way students think in solving problems in learning activities, independently and dare to argue which is indicated by lively discussions. In addition, there is an increase in the structure of language in students because students are trained to discuss regularly, searching for information through digital newspapers can open students' horizons and take full advantage of technological sophistication.Keywords: Digital Newspaper Media, Civic LiteracyDoi: https://doi.org/10.23960/JIPS/v5i1.37-42